Engaging EFL Students through KWL Strategy in Reading Comprehension: A Case Study of Four Students at a Junior High School in Karawang - Putri, Yulia Syafazira; Kamil, Acep Bahrum; Sumarta, Sumarta (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
Reading comprehension challenges the students’ understanding the meaning of the text. This study aim to exploring students’ behavioral engagement through KWL strategy in reading comprehension. The research method used in this study is descriptive case study with a qualitative approach. This research was conducted with limited to 4 students at eighth grade. The results showed that the KWL strategy gives students a better reading experience by enabling them to understand English text more quickly. The KWL strategy can make students more focused in learning reading comprehension. The KWL technique can also has encouraged students’ participation to learn more actively in analyzing the reading comprehension with peers and teacher. Finally, the KWL strategy can give teaching that builds students’ enthusiasm for developing their ability to reading comprehension; almost all students feel this enthusiasm after implementing the KWL strategy. This research suggest that teachers should expand or develop their teaching strategies to produce better learning experiences.